Room Temperature Corrosion Behavior of ZrB2-HfB2 Solid Solutions in Acidic and Basic Aqueous Environments. (20th August 2017) - Sitler, Steven J.; Charit, Indrajit; Raja, Krishnan S.
Abstract: Several solid solutions mixtures of ZrB2 and HfB2 with and without additives were investigated for corrosion behavior in aqueous solutions in a wide range of pH. The samples were prepared through ball milling followed by spark plasma sintering (SPS). In addition to the single component diborides and mixtures thereof, additives of Hf, Zr, and Ta pure metals as well as LaB6 and Gd2 O3 were mixed in to test for corrosion improvements. Several electrochemical methods were employed including potentiostatic polarization, potentiodynamic polarization and electrical impedance spectroscopy (EIS). The results showed that mixed diboride solid solutions had better corrosion resistance than their unmixed counterparts. ZrB2 -rich compositions performed better in the high pH solutions; whereas HfB2 -rich compositions showed better corrosion resistance under acidic conditions. Metal-rich compositions and Ta additions did not show improvements in the corrosion resistance, the addition of LaB6 to the Hf0.5 Zr0.5 B2 solid solution, however, exhibited enhanced corrosion resistance in non-acidic solutions.